Thorough characterization and stability of HP‐β‐cyclodextrin thymol inclusion complexes prepared by microwave technology: A required approach to a successful application in food industry - Rodríguez‐López, María Isabel; Mercader‐Ros, María Teresa; López‐Miranda, Santiago; Pellicer, José A; Pérez‐Garrido, Alfonso; Pérez‐Sánchez, Horacio; Núñez‐Delicado, Estrella; Gabaldón, José A (Journal of the science of food and agriculture, 2019)
BACKGROUND The aims of the present study were to obtain a stable dry powder formulation of cyclodextrins (CDs) encapsulating thymol, for successful use as an ingredient on an industrial scale, and to characterize the thymol‐CDs complexes using different techniques. RESULTS Thymol was successfully solubilized in aqueous solutions and the Kc value increased with the pH of the media until the pH was neutral, giving the highest values (2583 ± 176 L mol−1) for HP‐β‐cyclodextrins (HP‐β‐CDs). The best encapsulation efficiency of thymol in solid complexes was obtained using the microwave (MWI) encapsulation method. The different characterization techniques have demonstrated the affinity of HP‐β‐CDs for thymol molecules, forming stable complexes. CONCLUSIONS The results support the use of the MWI method in the preparation of solid HP‐β‐CD‐thymol complexes, due to greater encapsulation efficiency and technological and economic advantages for industrial applications. © 2018 Society of Chemical Industry